Leprosy and hepatitis B coinfection in southern Brazil - Leitão,Cleverson (2014)
To investigate the association of leprosy with hepatitis B virus (HBV) infection, as yet unknown for South Brazil, we assessed hepatitis B virus coinfection in 199 South Brazilian leprosy patients (119 lepromatous, 15 tuberculoid, 30 borderline, 12 undetermined and 23 unspecified) and in 681 matched blood donors by screening for the hepatitis B virus markers HBSAg and anti-HBc, using ELISA. Positive samples were retested and anti-HBc+ only samples were tested for the hepatitis B surface antibody (anti-HBs). There was a strong association between leprosy and hepatitis B virus infection (OR = 9.8, 95% CI = 6.4–14.7; p = 0.004·E−30), as well as an association between HBV infection and lepromatous leprosy, compared to other forms (OR = 2.4, 95% CI = 1.2–4.8; p = 0.017). We also found that confinement due to leprosy was associated with hepatitis B virus infection (OR = 3.9, 95% CI = 2.1–7.4; p = 0.015·E−3). Leprosy patients are susceptible to develop hepatitis B virus infection, especially lepromatous. Institutionalized patients, who probably present a stronger Th2 response, have higher risk of being exposed to hepatitis B virus. This clearly emphasizes the need for special care to leprosy patients in preventing hepatitis B virus coinfection in South Brazil.